Analysis of Anthropometric Parameters of Physical Development of Children with Adenoid Hypertrophy Before and After Adenoidectomy - N.P. Alimova (American Journal of Botany and Bioengineering, 2024)
The proportion of children with chronic adenotonsillitis varies from 20 to 50 per cent, and 37 to 70 per cent of frequently ill children. This indicates an increase in pharyngeal tonsil hypertrophy, an increase in the incidence of adenoid pathology in children, which adversely affects the structural formation of the jaw complex. It has been revealed that the influence of the long-term course of diseases in children leads to a violation of the formation of the facial skeleton, which is reflected in the form of a sagging lower jaw, its narrowing and distant, improper development of the hard palate and occlusion. In the development of dentoalveolar anomalies at the age of 8-10 years, diseases of the ENT organs, in particular, overgrowth of adenoids, play a significant role.